THE USE OF METAPHOR IN INVICTUS FILM - Theresia Theresia; Meisuri Meisuri (State University of Medan, 2013)
ABSTRACT The aims of this article are to find out the types of metaphor, and to describe the implication of the most dominant type of metaphor used in the Invictus film. By using documentary technique, six selected scene were taken randomly from the script, there were fifty dialogues uttered by Nelson Mandela used as the sample. The data were analyzed by using descriptive qualitative technique. It was found are six types of metaphor used in Invictus film and the most dominant type of metaphor is Subjective Metaphor. This implies that the films tends to show the portray of Nelson Mandela as the President of South Africa who is subjectively in constructing his ideas, opinions and message in the film about sport and apartheid. Keywords: film, Invictus, Metaphor